Male Compensatory Consumption in American History. (December 2020) - Witkowski, Terrence H.
The overcompensation thesis posits that men react to gender insecurities by demonstrating their masculinity in extreme ways, some of which include highly gendered forms of consumer behavior known as male compensatory consumption. Though such consumption can be relatively benign, even healthy and positive, several forms of male compensatory behavior might harm public safety, the environment, and social accord. Support for the thesis exists, but is not overwhelming and further research is needed. This article approaches compensatory consumption in the United States from a historical perspective. It presents evidence from four separate periods – circa 1900, the 1930s, the 1950s, and circa 2000 – showing cultural continuities and change in the meaning of masculinity, but also similarities and differences in the perceived threats, the groups of men most affected, and their responses. These historical findings provide macromarketing insights into the societal consequences of market behavior.